1992
DOI: 10.5980/jpnjurol1989.83.505
|View full text |Cite
|
Sign up to set email alerts
|

Fertility in Patients After Surgical Repair of Membranous Urethral Strictures Associated With Pelvic Fractures

Abstract: We evaluated fertility in fourteen patients after surgical repair of membranous urethral strictures associated with pelvic fractures. Eight patients were operated on using Badenoch's method (pull through) and six patients by end-to-end anastomosis of the urethra. All of them have maintained libido and potency after urethroplasty. No ejaculatory disturbance had ever occurred since surgery. Semen analysis was evaluated three months to four years after urethroplasty and serum hormone levels were measured in four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…Few studies have used formal semen analysis to assess ejaculation and fertility after PFUDD repair, and our study adds to the total provided by Iwamoto et al [6] in 1992. However, the present study has several limitations, the largest being the relatively few men assessed.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Few studies have used formal semen analysis to assess ejaculation and fertility after PFUDD repair, and our study adds to the total provided by Iwamoto et al [6] in 1992. However, the present study has several limitations, the largest being the relatively few men assessed.…”
Section: Discussionmentioning
confidence: 64%
“…In 1992 Iwamoto et al [6] similarly used semen analyses to evaluate fertility after PFUDD repair in patients in Japan. As in the present study, they found preservation of ejaculation in all 14 men evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…There are some specific articles that address fertility in the context of urethroplasty ( Table 8 ) [ 52 , 63 , 65 ]. These studies essentially describe the seminal parameters of patients having undergone posterior urethroplasty.…”
Section: Resultsmentioning
confidence: 99%
“…в своем исследовании не нашли разницы в частоте искривления полового члена у пациентов со стриктурами больше или меньше 2,5 см. Группы пациентов были неодонородны, малы (по 11 пациентов в каждой) и включали пациентов с неудачными пластиками и уретротомиями в анамнезе [39]. G. Barbagli также не сообщал о развитии искривления члена, фибротических изменений у пациентов после анастомотической пластики, поскольку показания к операции были ограничены протяженностью стриктуры <3 см [19].…”
Section: искривление полового членаunclassified